Local Community Involvement in Geotourism Hiking in Kampung Kinirasan, Ranau, Sabah - Elyria Crystta Johunis; Hamimah Talib; Rosmalina Abdul Rahsid; Kamlisa Uni Kamlun; Jennifer Chan Kim Lian (Penerbit UMS, 2021)
Geotourism is a form of sustainable tourism that focuses on the knowledge of the geological features of the earth by encouraging understanding, appreciation and conservation of the environment and culture as well as providing benefits to the local community. It was created to improve the well-being and standard of living of the local community through involvement in tourism while preserving the local environment, culture and heritage. This study was conducted to examine the level of readiness, acceptance and involvement of the local community in geotourism-hiking project around Bukit Balingkadus, Kampung Kinirasan, Ranau. Quantitative research is done by distributing questionnaires to the respondents. The results of the analysis showed that the local community is ready to get involved in the geotourism-hiking project. Incentives and returns earned will encourage their enthusiasm to be actively involved in this project. The project is also seen to be able to open new employment opportunities and raising the living standards of the local community. Cooperation between all parties is essential in order to achieve the sustainable development objectives of the geotourism-hiking project carried out. Further studies need to be conducted in the future.